Childhood maltreatment and identity diffusion among inpatient adolescents: The role of reflective function. (October 2019) - Penner, Francesca; Gambin, Malgorzata; Sharp, Carla
Abstract: Introduction: Identity integration, as opposed to identity diffusion, has been associated with greater self-esteem, meaning in life, and functioning. Trauma may have negative effects on identity; however, few studies have examined trauma and identity among adolescents, particularly those with psychiatric disorders. Moreover, factors that may promote healthy identity in adolescents who have experienced trauma have not been identified. This study aimed to test associations between childhood maltreatment and identity diffusion among adolescents with psychiatric disorders, and evaluated reflective function (RF) as a mediator of these associations. Methods: 107 adolescents ( M age = 15.36, 75.7% female) who were inpatient at a psychiatric hospital in the United States completed self-report measures of childhood maltreatment (physical, sexual, and emotional abuse; physical and emotional neglect; total maltreatment), identity diffusion, and RF. Path analysis was used to test two models of the relations between childhood maltreatment, RF, and identity diffusion. Results: Total maltreatment and all forms of maltreatment except physical abuse were significantly associated with identity diffusion at the bivariate level. In path analysis (Model 1), emotional and physical neglect were directly associated with identity diffusion, and RF mediated the association between emotional abuse and identity diffusion. In Model 2, RF partially mediated the association between overall level of maltreatment and identity diffusion. Conclusions: Emotional abuse, emotional neglect, physical neglect, and total combined maltreatment exposure may be risk factors for adolescent identity diffusion. Targeting RF may help to build healthy identity among adolescents with symptoms of psychiatric disorders who have experienced maltreatment, particularly emotional abuse.